In It to Win It? Self-Esteem and Income-Earning among Couples - Botea, Ioana; Donald, Aletheia; Rouanet, Lea (World Bank, Washington, DC, 2020)
This paper investigates whether the relative self-esteem level of spouses can lead to within- household competition for inputs and affect economic gender inequality in the home. Using data on smallholder farmer couples in Cote d'Ivoire, the paper examines the relationship between spouses' self-esteem and income-earning in agriculture. Although the link between own self-esteem and crop income earning is positive, there is a "battle of the sexes" in which one spouse's self-esteem is negatively related to the other's income earning, particularly income earning in higher-value, export-oriented agriculture. Women's outcomes are more sensitive to their own self-esteem (positively) and to their partners' (negatively) than men's. This negative relationship is driven by individuals during middle age, when self-esteem is considered most stable. A key channel through which self-esteem appears to matter is by increasing control over household land, which is a scarce but crucial input to agricultural production. In addition to confirming the importance of noncognitive skills for poverty reduction in rural settings, the findings highlight the importance of their impact on intra- and inter-household inequality, especially in the presence of interlocking market failures constraining the supply of inputs to production.